Dual-energy, standard and low-kVp contrast-enhanced CT-cholangiography: A comparative analysis of image quality and radiation exposure - Stiller, Wolfram; Schwarzwälder, Christoph Bernhard; Sommer, Christof-Matthias; Radeleff, Boris; Kauczor, Hans-Ulrich (European journal of radiology, 2012)
Objective Quantitative image quality assessment in terms of image noise (IN), contrast-to-noise ratio (CNR), and signal-to-noise ratio (SNR) in relation to required radiation dose (RD) for dual-energy (DE), standard and low-kVp contrast-enhanced computed-tomography (CT) cholangiography. Materials and methods For each of 22 DECT-cholangiography examinations, 3 image datasets were analyzed as independent single-source CT-acquisitions at different tube potential, i.e. 80kVp, 120kVp-equivalent (linear blended dataset M0.3: 30% 80kVp, 70% 140kVp), and 140kVp. Analysis comprised determination of IN, CNR and SNR in regions of interest (ROI) placed in liver parenchyma and contrasted bile ducts. IN was evaluated as mean standard deviation of 3 ROI placed within liver parenchyma (segments 6/7, 5/8, 2/3); CNR was assessed as bile duct-to-liver parenchyma ratio, and SNR as bile duct-to-image noise ratio. RD in terms of CT dose index (CTDIvol), dose-length product (DLP) and effective dose (ED) has been determined for each of the datasets, and compared to console prediction and scan summary values. Using phantom measurements of CTDIvol, a method for separating comprehensive RD values of DE-acquisitions into the original RD contribution of each tube (80kVp/140kVp) has been developed, enabling comparison of all 3 datasets as if independently acquired using single-source “single-energy” technique. Results Highest IN was detected for 80kVp- (38.6±5.1HU), lowest for 120kVp-equivalent linear blended M0.3-datasets (23.1±3.4HU) with significant differences between all datasets (P<0.001). Highest SNR and CNR were measured for M0.3- (SNR: 14.8±4.1; CNR: 11.6±3.8) and 80kVp-datasets (SNR: 13.8±4.8; CNR: 11.2±4.5); lowest for 140kVp-datasets (SNR: 9.5±2.5; CNR: 7.1±2.3) with significant differences between M0.3- and 140kVp-datasets as well as between 80kVp- and 140kVp-datasets (both P<0.001 for both CNR, SNR). CTDIvol, DLP and ED were reduced by 50% for low-kilovoltage acquisitions (CTDIvol: 5.5±1.4mGy; DLP: 127.8±40.1mGycm; ED: 1.9±0.6mSv) compared to comprehensive DE-acquisitions (CTDIvol: 11.0±2.3mGy; DLP: 253.8±67.5mGycm; ED: 3.8±1.0mSv, tube contribution: 80kVp: 44.5%; 140kVp: 55.5%), and by 20% compared to conventional acquisitions at 120kVp (CTDIvol: 6.71mGy; DLP: 153.5±16.9mGycm; ED: 2.3±0.3mSv). Conclusions Despite higher IN, low-kilovoltage CT-cholangiography reveals no significant difference with respect to CNR and SNR when compared to linear blended images yielded by DECT. Compared to DECT or conventional CT at 120kVp, contrast-enhanced low-kVp CT cholangiography potentially allows reduction of patient dose by up to 50% or 20%, respectively. Therefore, CT-cholangiography at 80kVp should be considered as an alternative to DECT-cholangiography whenever DECT is unavailable, or if increased image quality of DECT regarding quantitative bile duct evaluation is not needed for diagnosis.